User Compliance and Behavioral Adaptation Associated With Supine Avoidance Therapy. Issue 1 (2nd January 2018) - Levendowski, Daniel; Cunnington, David; Swieca, John; Westbrook, Philip
Abstract : This study investigates behavioral adaptation to vibrotactile position-avoidance therapy during sleep in patients with obstructive sleep apnea ( n =135) across 15 to 52 weeks. The overall compliance, based on nights used ≥ 4 hr, was 71%. Overall regular use, that is, ≥ 4 hr/night over 70% of nights, was 88%. Poor early compliance strongly predicted poor long-term treatment adherence, with 92% of those noncompliant across the first 12 weeks of therapy remaining noncompliant. Conversely, 21% of those with compliant utilization in the short term became noncompliant in the long term. It appears that patients do not habituate to the stimulus during sleep, nor was there a training effect associated with long-term use.